Impact of hypoxia on DNA repair and genome integrity - Kaplan, Alanna R; Glazer, Peter M (Mutagenesis, 2020)
Abstract Hypoxia is a hallmark of the tumour microenvironment with profound effects on tumour biology, influencing cancer progression, the development of metastasis and patient outcome. Hypoxia also contributes to genomic instability and mutation frequency by inhibiting DNA repair pathways. This review summarises the diverse mechanisms by which hypoxia affects DNA repair, including suppression of homology-directed repair, mismatch repair and base excision repair. We also discuss the effects of hypoxia mimetics and agents that induce hypoxia on DNA repair, and we highlight areas of potential clinical relevance as well as future directions.